Leptin gene polymorphism in association with lactation milk yield in Murrah buffaloes - JAMUNA, V; GUPTA, A K; CHAKRAVARTY, A K; SINGH, AVTAR; PATIL, C S; KUMAR, MANOJ; VOHRA, VIKAS (The Indian Journal of Animal Sciences, 2016)
PCR amplification of exon-2 of leptin gene yielded an amplified product of 210 bp in Murrah buffaloes. RFLP of leptin gene done with Aci1 restriction enzyme revealed 3 types of genotypes CC, TC and TT in Murrah buffaloes of NDRI herd with a frequency of 0.26 , 0.73 and 0.013% respectively. Results suggested that CC genotype of leptin gene in Murrah buffaloes is significantly associated with 305 days milk yield. Overall study suggested the scope of considering genetic information of leptin gene in breeding and management strategies for the improvement of Murrah buffaloes of NDRI herd.